2021
DOI: 10.1016/j.jcot.2021.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Does racial background influence outcomes following total joint arthroplasty?

Abstract: Background: The purpose of this study is to assess whether racial differences influence patient-reported outcome measures (PROMs) following primary total hip (THA) and knee (TKA) arthroplasty. Methods: We retrospectively reviewed patients who underwent primary THA or TKA from 2016 to 2020 with available PROMs. Both THA and TKA patients were separated into three groups based on their ethnicity: Caucasian, African-American, and other races. Patient demographics, clinical data, and PROMs at various time-periods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…1,2 Prior research has demonstrated disparities in access to care and outcomes after joint arthroplasty operations. [3][4][5] Singh et al 3 found that African American patients had longer average length Matthew Orringer, BA…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Prior research has demonstrated disparities in access to care and outcomes after joint arthroplasty operations. [3][4][5] Singh et al 3 found that African American patients had longer average length Matthew Orringer, BA…”
mentioning
confidence: 99%
“… 1 , 2 Prior research has demonstrated disparities in access to care and outcomes after joint arthroplasty operations. 3 - 5 Singh et al 3 found that African American patients had longer average length of stay after both THA and total knee arthroplasty (TKA), while White patients had higher patient-reported outcome measure scores. Another study found that White patients, those with commercial insurance coverage, and those earning greater than $25,000 per year had a shorter average length of stay.…”
mentioning
confidence: 99%
“…Additionally, it is possible that some of the low volume facilities are "safety net" hospitals, which could explain some of the socioeconomic differences between patient populations seen in the study. Overall, such differences in patient populations raise concerns regarding patient care, especially considering that non-White patients have reported lower patient-reported outcome measures [33]. Naturally, these findings suggest interconnected and multifactorial causes and thus require further investigation to yield effective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that compared to Caucasian patients, African-American patients demonstrated lower PROM scores following TJA. Surgical-time and length-of-stay significantly differed between the groups (p < 0.001); Black patients who underwent THA required the longest operative time and spent longer in hospital following THA/TKA compared to White patients [67].…”
Section: Utilization Of Other Treatments Apart From Surgery and Treatment Recommendationsmentioning
confidence: 96%
“…Another study, performed by Singh and colleagues, investigated whether racial differences influenced patient-reported outcome measures (PROMs) following primary THA and TKA between 2016 and 2020 [67]. Participants included 1999 THA patients and 1375 TKA patients.…”
Section: Utilization Of Other Treatments Apart From Surgery and Treatment Recommendationsmentioning
confidence: 99%